Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/jcla.24028
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lncRNA‐associated competing endogenous RNA networks for occurrence and prognosis of gastric carcinoma

Abstract: Gastric cancer (GC) is one of the most frequent digestive system cancers and is the second cause of cancer mortality worldwide by 2018. 1 The cases in China account for more than 40% of the total number of GC worldwide due to a high incidence rate and a large population. 2 Moreover, the GC patients were more likely to be in the advanced stage when diagnosed because of non-early specific symptoms.Unfortunately, the late diagnosis can significantly affect the 5-year survival rate. In the past decade, due to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Finally, we constructed the LINC00702-miR-181b-5p-SPP1 axis and showed that this signal axis could regulate the development of CAVD. As one of the miRNA sponges, LINC00702 could interact with different miRNAs in various diseases (60)(61)(62)(63). By constructing a cardiac hypertrophyrelated LncRNA-mRNA network, Song et al reported that LINC00702 was one of the ten hub nodes (64).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we constructed the LINC00702-miR-181b-5p-SPP1 axis and showed that this signal axis could regulate the development of CAVD. As one of the miRNA sponges, LINC00702 could interact with different miRNAs in various diseases (60)(61)(62)(63). By constructing a cardiac hypertrophyrelated LncRNA-mRNA network, Song et al reported that LINC00702 was one of the ten hub nodes (64).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical information was gathered, including TNM stage, pathological grade, age, gender, follow-up period, and survival status. In this study, 22 genes associated with cuproptosis were chosen for examination based on previously published studies [ 7 , 12 , 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Two studies with unclear basis of HR calculation and the reference group (even after mailing) were excluded in meta-analysis (15,16). The pooled examination of HRs with 95% CI of univariate survival results was performed based on the 11 studies, in which sample sizes were reported (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Besides, according to the information of multivariate survival analysis, the pooled HRs with 95% CI was calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Among studies with univariate survival analysis, 11 studies with reported sample size, HR (with clear basis of calculation), and CI were identified for meta-analysis (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). These studies included 70 lncRNAs (including unique and repeated lncRNAs).…”
Section: The Prognostic Significance Of Lncrnasmentioning
confidence: 99%